2017
DOI: 10.1080/07391102.2017.1338164
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs as potential treatment option for preventing amyloid β toxicity in Alzheimer’s disease: an investigation by docking, molecular dynamics, and DFT studies

Abstract: Aggregation of amyloid beta (Aβ) protein considered as one of contributors in development of Alzheimer's disease (AD). Several investigations have identified the importance of non-steroidal anti-inflammatory drugs (NSAIDs) as Aβ aggregation inhibitors. Here, we have examined the binding interactions of 24 NSAIDs belonging to eight different classes, with Aβ fibrils by exploiting docking and molecular dynamics studies. Minimum energy conformation of the docked NSAIDs were further optimized by density functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 104 publications
1
58
0
Order By: Relevance
“…The docking protocol used in the present study was therefore validated by docking all native co‐crystallized ligand molecules to their respective proteins (PDB code: 2GV9, 2KI5, 5GMZ, 4A92 and 2HAL). According to the reported method of validation, if the RMSD (root mean square deviation) of the best‐docked conformation is ≤2.0 Å from the experimental one, the used scoring function is deemed to be successful . The RMSD values of the native co‐crystallized ligands after docking were ≤2.0 Å (data not shown), which confirms the reliability of AutoDock 4.2 for docking vitexin into crystal structures of different antiviral drug targets.…”
Section: Resultsmentioning
confidence: 99%
“…The docking protocol used in the present study was therefore validated by docking all native co‐crystallized ligand molecules to their respective proteins (PDB code: 2GV9, 2KI5, 5GMZ, 4A92 and 2HAL). According to the reported method of validation, if the RMSD (root mean square deviation) of the best‐docked conformation is ≤2.0 Å from the experimental one, the used scoring function is deemed to be successful . The RMSD values of the native co‐crystallized ligands after docking were ≤2.0 Å (data not shown), which confirms the reliability of AutoDock 4.2 for docking vitexin into crystal structures of different antiviral drug targets.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of NSAIDs may exert a protective effect on neuronal cells by inhibiting cyclooxygenase (COX) activity, especially COX-2, whose expression is strongly induced by inflammatory signals [19]. Several papers describe a relationship between long-term use of NSAIDs and a reduced risk of cognitive impairment, as well as a slower decline in cognitive function [18,30]. However, the mechanism of protective action has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Some NSAIDs have been shown to be potential inhibitors of β-amyloid fibril formation. They can also activate the expression of other proteins that prevent Aβ aggregation or interact via peroxisome proliferator-activated receptors (PPARs) [18,33,34]. It has also been found that these drugs may affect the processing of amyloid precursor protein (APP) by βand γ-secretases [35].…”
Section: Discussionmentioning
confidence: 99%
“…Frontier molecular orbital features HOMO, LUMO were calculated at the same level of theory. For each of the compounds, HOMO-LUMO gap, hardness (η), softness (S), and chemical potential (μ) were calculated from the energies of frontier HOMOs and LUMOs as previously reported [31] considering Parr and Pearson interpretation [32,33] of DFT and Koopmans theorem [34].…”
Section: Geometry Optimization Of All Schiff Base and Their Metal Commentioning
confidence: 99%